2016
DOI: 10.18240/ijo.2016.08.08
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc area in different types of glaucoma

Abstract: Disc size affects the retinal nerve fiber layer thickness in eyes with primary open angle glaucoma and is a possible risk factor for glaucomatous optic nerve damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, early diagnosis and management of glaucoma can effectively reduce its damage to the tissue of the optic nerve and preserve eyesight. In clinical treatment, doctors usually diagnose glaucoma through the size of the intraocular pressure (the normal range is 10–21 mmHg), the vertical diameter ratio of the optic cup (OC) to the optic disc (OD), and the angle between the cornea and the iris [ 2 ]. The detection of the optic disc in the retinal fundus images plays an important role in the diagnosis of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early diagnosis and management of glaucoma can effectively reduce its damage to the tissue of the optic nerve and preserve eyesight. In clinical treatment, doctors usually diagnose glaucoma through the size of the intraocular pressure (the normal range is 10–21 mmHg), the vertical diameter ratio of the optic cup (OC) to the optic disc (OD), and the angle between the cornea and the iris [ 2 ]. The detection of the optic disc in the retinal fundus images plays an important role in the diagnosis of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…In glaucoma, cupping is associated with optic canal expansion [2]. Indeed, previous studies have reported that increased disc area may be associated with glaucoma [5] and that canal expansion occurs with increasing intraocular pressure [6]. Our goal was to analyze whether canal expansion in glaucoma can be used to differentiate suprasellar tumors from glaucoma using optic nerve head OCT images.…”
Section: Introductionmentioning
confidence: 99%